2014
DOI: 10.1128/aac.03337-14
|View full text |Cite
|
Sign up to set email alerts
|

Complex Polymorphisms in the Plasmodium falciparum Multidrug Resistance Protein 2 Gene and Its Contribution to Antimalarial Response

Abstract: k Plasmodium falciparum has the capacity to escape the actions of essentially all antimalarial drugs. ATP-binding cassette (ABC) transporter proteins are known to cause multidrug resistance in a large range of organisms, including the Apicomplexa parasites. P. falciparum genome analysis has revealed two genes coding for the multidrug resistance protein (MRP) type of ABC transporters: Pfmrp1, previously associated with decreased parasite drug susceptibility, and the poorly studied Pfmrp2. The role of Pfmrp2 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…The most skewed region contains five genes (Fig 4C) including pfmrp2 ( PF3D7_1229100 ) at the center of the peak. Pfmrp2 has high genetic variability among Thai clinical isolates with single genetic variants having significant associations with in vitro response to chloroquine, mefloquine and piperaquine and in vivo parasite clearance [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most skewed region contains five genes (Fig 4C) including pfmrp2 ( PF3D7_1229100 ) at the center of the peak. Pfmrp2 has high genetic variability among Thai clinical isolates with single genetic variants having significant associations with in vitro response to chloroquine, mefloquine and piperaquine and in vivo parasite clearance [32].…”
Section: Resultsmentioning
confidence: 99%
“…The most skewed region on chromosome 12 overlaps with the selected region in a uncloned bulk culture of MKK2835 x NHP1337 cross F 1 progeny except that selection is against the derived allele in pfmrp2 in this case. Pfmrp2 has been associated with mefloquine and piperaquine response in vitro and parasite clearance [32] in Thai isolates and we speculate it may have a fitness cost in vitro. The role pfmrp2 plays in drug resistance is still unclear and these genetic crosses may help elucidate its function.…”
Section: Discussionmentioning
confidence: 99%
“…In P. falciparum, resistance to CQ is conferred through the K76T mutation in the chloroquine resistance transporter gene (Pfcrt) (13). Additionally, mutations identified in the P. falciparum multidrug resistance (Pfmdr), Na + /H + exchanger (Pfnhe), and multidrug resistance-associated protein (Pfmrp1 and Pfmrp2) genes are known to contribute to quinoline resistance mechanisms (14)(15)(16). Lastly, primaquine is distinct from CQ and MQ in that it is the only clinically approved drug for treatment of relapsing malaria caused primarily by P. vivax hypnozoites.…”
Section: Challenges and Current State Of Malaria Drug Developmentmentioning
confidence: 99%
“…Mutations in the gene encoding for P. falciparum MRP1 have been associated with increased resistance to antimalarials sulfadoxine-pyrimethamine, chloroquine and quinine, although its definitive role in drug responses remains controversial (Mu et al, 2003, Klokouzas et al, 2004, Dahlstrom et al, 2009b. In addition, evidence has been presented that increased MRP2 expression confers tolerance to quinolone drugs (Mok et al, 2013), and the high genetic variability in Pfmrp2 has been associated with reduced quinoline sensitivity (Veiga et al, 2014). We have previously shown that both MRP1 and MRP2 of P. falciparum are located on the plasma membrane of blood stage parasites , indicating that MRP-mediated transport may play a role in parasite growth within the erythrocyte.…”
Section: Introductionmentioning
confidence: 99%